2008
DOI: 10.1063/1.2953090
|View full text |Cite
|
Sign up to set email alerts
|

Creation of nanopatterns by local protonation of P4VP via dip pen nanolithography

Abstract: The elastic mechanical response of a poly͑4-vinylpyridine͒ film is exploited to create nanostructures under ambient conditions via dip pen nanolithography. Using a pH 4 phosphate buffer solution as the "ink," a series of experimental results indicates that the nanometer-sized structures are due to local swelling of the film's pyridyl groups upon their protonation with the hydronium ions delivered by the tip. Control over the structures' height is gained by properly selecting the writing velocities or the dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Several control experiments confirmed that an AFM tip, when coated with phosphate buffer solution of pH 4 and placed in contact with the substrate, delivers protons into the P4VP polymer film causing the latter to swell. [18] A similar result has been shown before in a macroscale setup, where an increase in film thickness of UV-cross-linked P4VP films under acidic stimulation was found. [19] This swelling is due to the protonation of pyridyl groups when adding Brønsted acids to form pyridinium ions, which was confirmed by infrared spectroscopy which showed a shift in the frequency band associated with the pyridyl ring-stretching modes to frequencies related to pyridinium ions.…”
Section: Introductionsupporting
confidence: 85%
“…Several control experiments confirmed that an AFM tip, when coated with phosphate buffer solution of pH 4 and placed in contact with the substrate, delivers protons into the P4VP polymer film causing the latter to swell. [18] A similar result has been shown before in a macroscale setup, where an increase in film thickness of UV-cross-linked P4VP films under acidic stimulation was found. [19] This swelling is due to the protonation of pyridyl groups when adding Brønsted acids to form pyridinium ions, which was confirmed by infrared spectroscopy which showed a shift in the frequency band associated with the pyridyl ring-stretching modes to frequencies related to pyridinium ions.…”
Section: Introductionsupporting
confidence: 85%
“…To further support the claim that the presence of raised patterns were a consequence of the swelling response of the P4VP polymer film , , we demonstrated the reversibility of the patterning process by selectively erasing an existing swollen pattern. “Dot” features were initially generated using a tip coated with the acidic ink.…”
Section: Resultsmentioning
confidence: 71%
“…The factors that affect the dimensions of the patterned features can be attributed but not limited to a combination of several variables, such as the writing speed (14,34,35), the effects of temperature and humidity (19,34,36), and the geometry and wettability of the tip (36). The dimensions of dot features as a function of the dwell time and relative humidity has been demonstrated in our previous work (26,27). No structures could be created when the humidity was below 30%.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…[10][11][12] We have developed a simple photochemical immobilization technique for the fabrication of polymer thin films on solid substrates. [13][14][15] The method is based on the photochemistry of polymers. Upon UV irradiation, free radicals are generated and can undergo crosslinking, degradation, and chain scission reactions.…”
mentioning
confidence: 99%